Problems in verb conjugation in Spanish among Malaysian Chinese students: A case study - Vasquez, Edison Mejia (Journal of Modern Languages, 2017)
This study examines the written production of four Malaysian Chinese students at two different levels in their study. More specifically, this study employs Error Analysis to determine the type of errors committed in verb conjugations when they were in the middle of the first semester (Spanish 1) and in the middle of the second semester (Spanish 3) of their undergraduate Spanish language and linguistics programme. A distinction is made between "error" and "mistake" and how both terms are interrelated and apply to the data studied. The errors were classified not only according to the different error categories drawn by Brown (2000) but also according to the different grammatical functions they served. The results revealed that errors in verb conjugation in Spanish do not have anything to do with how many languages they speak or how inflected a target language may be, but rather are influenced by other different and yet interrelated aspects in second language acquisition such as linguistic input and individual differences. This raises crucial theoretical questions as to whether L2 acquisition is influenced by the environmental factors that govern the input to which learners are exposed, or of intemal mental factors which somehow dictate how learners acquire grammatical structures. Moreover, it was found that if problems in conjugating verbs in Spanish are to be attributable to one phenomenon, that phenomenon is intraference and not so much interference.